多孔介质中甲烷水合物的生成特性研究进展 - 臧小亚; 梁德青; 吴能友 (2015)
Natural gas hydrate is a clean and efficient energy source and it was found abundantly in natural sediment pores under the deep sea. Gas hydrate also can be used as a means of gas storage and separation technology. Therefore, hydrate formation in porous m